Preparation method and application of PI / S-AGO composite wave-absorbing film
By compounding sulfur-doped amino graphene oxide with polyimide, a PI/S-AGO composite absorbing film was prepared, which solved the problem of secondary radiation caused by the polyimide film's reliance on reflection, achieved high-efficiency absorbing performance and broadband absorption, and improved the stability and compatibility of the material.
Patent Information
- Application Number
- CN202510874959.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-12
AI Technical Summary
Existing polyimide films as electromagnetic protection materials mainly rely on electromagnetic wave reflection, which leads to secondary electromagnetic radiation pollution. In addition, traditional preparation methods have problems such as expensive equipment, low material utilization, and easy oxidation and failure of fillers.
Sulfur-doped amino-modified graphene oxide (S-AGO) was composited with polyimide (PI). By introducing sulfur atoms into graphene to form defects and functional groups, the dielectric loss capacity of the composite material was improved, and the PI/S-AGO composite absorbing film was prepared.
The absorbing performance has been significantly improved, achieving a reflection loss of -65.8 dB in the Ka band and an effective absorption bandwidth of 6.42 GHz. It has broken through the thickness limitation of traditional absorbing materials, enhanced the polarization loss mechanism and structural stability, and has good compatibility and high environmental protection.
Smart Images

Figure CN120623532A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of absorbing materials, and in particular relates to a preparation method and application of a polyimide / sulfur-doped amino-graphene oxide composite absorbing film. Background Art
[0002] The rapid development and widespread application of electromagnetic waves have greatly promoted the advancement of communication networks, remote sensing, medical imaging, automobiles, radar systems, nondestructive testing, and numerous other emerging technologies. However, excessive electromagnetic waves lead to the accumulation of electromagnetic radiation in the environment, causing electromagnetic pollution. This pollution not only poses a potential threat to human health but also has the potential to disrupt ecological balance.
[0003] In this context, electromagnetic protection materials that can absorb or reflect electromagnetic waves to reduce radiation have become an important means of combating electromagnetic pollution. Absorbing materials, in particular, effectively prevent secondary pollution by absorbing electromagnetic waves into the material and dissipating them through methods such as heat, and have therefore become a research hotspot.
[0004] Polyimide (PI) offers unique advantages in the field of microwave-absorbing materials due to its excellent high-temperature resistance, high insulation, good mechanical properties, chemical corrosion resistance, and low dielectric constant. However, it should be noted that most polyimide films used as electromagnetic shielding materials rely primarily on their electromagnetic wave reflection properties to achieve shielding, which inevitably leads to secondary electromagnetic radiation pollution.
[0005] To address this issue, researchers have begun exploring the use of polyimide films as microwave absorbing materials. Currently, there are two main preparation methods: 1. Surface deposition / sputtering: For example, Andriyanti et al. used DC sputtering to deposit a gadolinium-doped cerium oxide-barium ferrite (GDC-BaFe2O4) thin film on a PI (Kapton) substrate to create a microwave absorbing film. The sample thickness was 70.5 μm at a sputtering time of 7.5 minutes, and the film achieved an RL of -39.6 dB at 10 GHz. min 2. Filler composite / blending method: For example, Zeng et al. prepared a multifunctional polyimide composite material doped with niobium pentoxide / carbon nanotube microspheres (NBCP). The results showed that when the volume filling amount of NBCP was 15%, the thickness of the composite material was 2.09 mm and its RL min The material exhibits excellent mechanical properties and a thermal insulation temperature difference of over 100°C in a 150°C thermal environment.
[0006] However, both mainstream methods have limitations: the sputtering method is expensive, has low material utilization and is prone to damage to the substrate; and the absorbing fillers (such as carbon materials) introduced by the composite thin film method are easily oxidized and fail at high temperatures, affecting long-term stability, and the interface defects between the filler and the substrate will reduce the flexibility and mechanical strength of the film.
[0007] Given that the research on the above-mentioned polyimide absorbing films is still immature, the present invention focuses on improving the absorbing performance of polyimide / graphene composite films, aiming to optimize existing methods or explore new approaches to address the above-mentioned limitations. Summary of the Invention
[0008] In view of this, the present invention provides a method for preparing a polyimide / sulfur-doped amino-graphene oxide composite absorbing film, which introduces S atoms to generate a large number of defects and functional groups in graphene, thereby improving the dielectric loss capacity of the composite material.
[0009] The present invention adopts the following technical solutions: A method for preparing a polyimide / sulfur-doped amino-graphene oxide composite absorbing film comprises the following steps: (1) Preparation of AGO Graphene oxide was first dispersed in deionized water and ultrasonically treated, and then p-phenylenediamine was added. The mixture was stirred and reacted in an oil bath at 75-85°C for 10-15 hours. After the reaction was completed, the mixture was filtered, washed, and vacuum-dried to obtain amino-modified graphene oxide, denoted as AGO. The mass ratio of graphene oxide to p-phenylenediamine was 1:2-2:1.
[0010] (2) Preparation of S-AGO Under reflux conditions at 90-100° C., a sodium polysulfide solution is added dropwise to an AGO dispersion at a rate of 1-5 mL / min for 3-6 hours. After the reaction, the graphene is filtered, washed, and vacuum-dried to obtain sulfur-doped graphene, which is designated as S-AGO. The concentration of the sodium polysulfide solution is 2-2.5 mol / L in terms of sodium ions, and the concentration of the AGO dispersion is 0.001-0.005 g / mL.
[0011] (3) Preparation of PI / S-AGO composite film First, under inert atmosphere, S-AGO was dispersed in N,N-dimethylacetamide and stirred evenly. 4,4'-diaminodiphenyl ether was added to dissolve it, and then 3,3',4,4'-benzophenonetetracarboxylic dianhydride was added in batches. The molar ratio of 4,4'-diaminodiphenyl ether to 3,3',4,4'-benzophenonetetracarboxylic dianhydride was 1:1.01-1.05. The mixture was then reacted at a low temperature of 0-5°C for 3-6 hours and allowed to stand overnight to obtain a uniform mixed solution with an S-AGO content of 0.5-5.0 wt%, named PAA / S-AGO solution. Next, the PAA / S-AGO solution was coated to form a film. After solvent evaporation and preliminary imidization at 80-120°C, the temperature was programmed to rise to 300-400°C in a tube furnace for complete imidization to obtain a PI / Cu / S-AGO composite film.
[0012] The complete imidization procedure is as follows: heating at 2°C / min, keeping at 150°C, 200°C, 250°C, and 300°C for 1 hour each; when the target temperature is 400°C, continue to keep at 350°C for 10 minutes and 400°C for 1 hour.
[0013] The PI / S-AGO composite film prepared by the present invention has a RL of 0.9-1.1 mm in the K band (18-26.5 GHz). min ≤-50dB, EAB≥3.0GHz; in Ka band (26.5~40GHz), when the film thickness is 2.5~3.5 mm: reflection loss RL min ≤-40 dB, effective absorption bandwidth EAB≥5.0 GHz, especially at 34.8 GHz, RL min ≤-65.8 dB, EAB≥6.42 GHz.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. Significantly improved wave absorption performance Achieved -65.8dB return loss at 34.8 GHz in the Ka-band ( Figure 12 a), effective absorption bandwidth 6.42 GHz (corresponding to thickness 3.15 mm), which is better than that of undoped PI / AGO system (PI / AGO-2.4 has an RL of 30.5 GHz). min =-61.2 dB) high-frequency absorption performance is further improved; Even at the ultra-thin thickness of 0.96 mm in the K band, RL min =-53.6 dB ( Figure 10 d, PI / S-AGO-2.8), breaking through the thickness limit of traditional absorbing materials.
[0015] 2. Enhanced polarization loss mechanism Sulfur doping forms C-S bonds (XPS 162.38 eV, Figure 3 d) and introduce lattice defects to enhance interface polarization: the number of Cole-Cole semicircles in the Ka band increases and the radius increases ( Figure 8 vs Figure 6 ); Dipolar polarization enhancement: the maximum value of the imaginary part of dielectric loss reaches 4.21 ( Figure 5 b), compared with PI / AGO (2.94, Figure 4 b) 43% increase.
[0016] 3. Improved structural stability Sulfur atoms are chemically bonded (CS / S 2- ) is stably embedded, and after imidization at 300℃: the elements are evenly distributed: EDS shows that the S element is evenly distributed in the film cross section ( Figure 1 d); The molecular structure is intact: FTIR maintains the characteristic peak of imide (1776 cm -1 C=O, Figure 2 ).
[0017] 4. Process compatibility and environmental protection High raw material utilization rate: sulfur doping reaction is carried out in the aqueous phase without organic solvent pollution; Compatible with traditional PI process: Gradient imidization (150-300℃) is consistent with the standard production line. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 SEM images of (ab) PI / S-AGO-2.0 surface and (cd) PI / S-AGO-2.0 cross-section prepared in examples of the present invention.
[0019] Figure 2 FTIR spectra of S-AGO and PI / S-AGO-2.0 prepared in the examples of the present invention.
[0020] Figure 3 XPS spectra of PI / S-AGO-2.0 prepared according to the present invention: (a) full spectrum, (b) C 1s, (c) N 1s, and (d) S 2p.
[0021] Figure 4 Real part of the complex permittivity of the PI / AGO prepared in an embodiment of the present invention in (a) K-band, (b) imaginary part of the complex permittivity of the K-band, (c) dielectric loss tangent of the K-band, (d) real part of the complex permittivity of the Ka-band, (e) real part of the complex permittivity of the Ka-band, and (f) dielectric loss tangent of the Ka-band.
[0022] Figure 5 (a) Real part of the complex permittivity of the PI / S-AGO prepared in an embodiment of the present invention in the K band, (b) Imaginary part of the complex permittivity of the K band, (c) Dielectric loss tangent of the K band, (d) Real part of the complex permittivity of the Ka band, (e) Real part of the complex permittivity of the Ka band, and (f) Dielectric loss tangent of the Ka band.
[0023] Figure 6 Cole-Cole curves of PI / AGO-1.6 prepared in an embodiment of the present invention in (a) the K band and (b) the Ka band.
[0024] Figure 7 Cole-Cole curves of PI / S-AGO prepared in the embodiments of the present invention in the K band: (a) PI / S-AGO-1.6, (b) PI / S-AGO-2.0, (c) PI / S-AGO-2.4, and (d) PI / S-AGO-2.8.
[0025] Figure 8 Cole-Cole curves of PI / S-AGO prepared in the embodiments of the present invention in the Ka band: (a) PI / S-AGO-1.6, (b) PI / S-AGO-2.0, (c) PI / S-AGO-2.4, and (d) PI / S-AGO-2.8.
[0026] Figure 9 The reflection loss of the PI / AGO composite films prepared in accordance with the present invention varies with thickness at different graphene contents in the K band; (a) PI / AGO-1.6, (b) PI / AGO-2.0, (c) PI / AGO-2.4, and (d) PI / AGO-2.8.
[0027] Figure 10 Reflection loss of PI / S-AGO prepared according to the embodiment of the present invention in the K band as a function of thickness: (a) PI / S-AGO-1.6, (b) PI / S-AGO-2.0, (c) PI / S-AGO-2.4, and (d) PI / S-AGO-2.8.
[0028] Figure 11 The reflection loss of the PI / AGO composite films prepared in accordance with the present invention varies with thickness at different graphene contents in the Ka band; among them, (a) PI / AGO-1.6, (b) PI / AGO-2.0, (c) PI / AGO-2.4, and (d) PI / AGO-2.8.
[0029] Figure 12 Reflection loss of PI / S-AGO prepared in accordance with the present invention in the Ka band as a function of thickness: (a) PI / S-AGO-1.6, (b) PI / S-AGO-2.0, (c) PI / S-AGO-2.4, and (d) PI / S-AGO-2.8.
[0030] Figure 13 Impedance matching diagram of the PI / S-AGO prepared in an embodiment of the present invention in (a) K band, (b) Ka band, (c) K band, and (d) Ka band. DETAILED DESCRIPTION
[0031] The present invention will be further explained below with reference to specific embodiments. Example
[0032] 1. Preparation of AGO 0.1 g of graphene oxide (GO) was added to 100 mL of deionized water, and 0.1 g of p-phenylenediamine (PPDA) was added to 10 mL of deionized water. The mixture was simultaneously sonicated for 1 h to obtain a GO dispersion and a PPDA solution. The GO dispersion was then transferred to a three-necked flask, heated to 80°C, and the PPDA solution was added. The mixture was then magnetically stirred in an 80°C oil bath for 12 h. After the reaction, the mixture was filtered and washed several times with deionized water. Finally, the black powder was dried in an oven at 80°C to obtain amino-modified graphene oxide powder, designated AGO.
[0033] 2. Preparation of S-AGO (1) Na2S x Solution preparation: 9.6 g of elemental sulfur and 36 g of sodium sulfide nonahydrate (Na2S•9H2O) (M=240 g / mol) were added to 150 mL of deionized water and stirred magnetically for 1 h to obtain orange-yellow Na2S x solution; (2) Disperse 0.45g of AGO powder in 150mL of distilled water, ultrasonicate for 0.5h and transfer to a three-necked flask. x The solution was slowly added to the AGO solution and refluxed at 95°C for 4 hours under magnetic stirring. Finally, the solution was filtered, dried in an oven at 80°C, and ground into powder to obtain sulfur-doped graphene, which was recorded as S-AGO.
[0034] 3. Preparation of PI / S-AGO composite film Taking PI / S-AGO-1.6 composite film as an example, the preparation process of PI / S-AGO composite films with different S-AGO contents is introduced.
[0035] (1) Preparation of PAA / S-AGO solution: 0.0725 g of S-AGO powder was dispersed in 20 mL of DMAc for 3 h. Under N2 atmosphere, 1.6642 g of 4-4'-diaminodiphenyl ether (ODA) was added and magnetically stirred until completely dissolved. A total of 2.7863 g of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) was added in 5 portions, with a molar ratio of ODA to BTDA of 1:1.02. The reaction was continued in an ice bath at 0-5 °C for 5 h. After the reaction was completed, the solution was allowed to stand overnight. The solid content of the obtained PAA / S-AGO solution was 19% and the S-AGO content was 1.6 wt%, and it was named PAA / S-AGO-1.6. The remaining content formula is shown in Table 1.
[0036] Table 1 Formulations of polyamic acid solutions with different S-AGO contents (2) Preparation of PI / S-AGO composite film: The above PAA / S-AGO solution was coated with a wet film of 1.0 mm, and the solvent was evaporated at room temperature. After complete drying, the film was placed in an oven at 100°C for 1 hour for preliminary thermal imidization. After cooling naturally to room temperature, the film was demoulded in deionized water and transferred to a tube furnace. Under an argon atmosphere, the temperature was programmed to 300°C for complete thermal imidization. The specific procedure was 150°C for 1 hour, 200°C for 1 hour, 250°C for 1 hour, and 300°C for 1 hour, with a heating rate of 2°C / min. After the tube furnace was cooled naturally to room temperature, it was taken out to obtain PI / S-AGO-1.6. Other samples were prepared in the same way.
[0037] Note: The preparation of PI / AGO-1.6, PI / AGO-2.0, PI / AGO-2.4 and PI / AGO-2.8 is just to omit the "preparation of S-AGO" step! The structural characterization and performance evaluation of the samples prepared in the above examples are as follows: 1. Structural characterization (1) Figure 1 This is the SEM image of PI / S-AGO-2.0. Figure 1 (ab) It can be seen that the surface of the film is smooth and the graphene is evenly dispersed without agglomeration. Figure 1 (c) The graphene structure shows that the number of graphene in the upper half is significantly less than that in the lower half. This may be because after the PAA / AGO solution is coated, during the long solvent evaporation process, the graphene settles in the lower half of the film under the action of gravity. Figure 1 (d) Cross-section of PI / S-AGO-2.0, showing a distinct graphene layered structure. Based on the above analysis, it can be concluded that the PI / S-AGO composite film was successfully prepared. Furthermore, EDS analysis reveals that the elements C, N, O, and S are uniformly distributed across the cross-section of the material, with atomic percentages of 78.46%, 4.31%, 17.17%, and 0.06%, respectively.
[0038] (2) FTIR test Figure 2 The FTIR curves of S-AGO and PI / S-AGO-2.0 are shown in Figure 2, where “-300” represents the imidization temperature. S-AGO has a peak at 1617 cm -1 The absorption peak at 1363 cm -1 There is an obvious CN stretching vibration peak at 3432 cm, which confirms that the amino group is successfully grafted onto GO.-1 The absorption peak at 1776 cm represents the stretching vibration peak of the CN bond; -1 The absorption peak at 775 cm represents the C=O asymmetric stretching vibration peak; -1 The absorption peak at 1617 cm represents the bending vibration peak of the C=O bond and the deformation vibration peak of the imide ring; -1 The absorption peak at 1363 cm represents the C=C vibration peak of the aromatic carbon skeleton; and -1 The absorption peak at 1776 cm represents the CN stretching vibration peak. -1 and 1722 cm -1 The C=O asymmetric stretching vibration and C=O symmetric stretching vibration at are both characteristic peaks of polyimide.
[0039] (3) XPS test Figure 3 This is the XPS graph of PI / S-AGO-2.0. Figure 3 In (a), it can be seen that the sample contains four elements: C, N, O, and S. The presence of S element indicates that S-AGO has been successfully prepared. Figure 3 As shown in (b), the fitting peaks at 284.38 eV, 284.8 eV and 288.08 eV represent C=C, CN / CS and C=O, respectively. In the N 1s spectrum, the peak at 398.38 eV is the -N= bond, the peak at 399.68 eV is the CN bond, and the peak at 400.88 eV is the -NR3 + ( Figure 3 (c)). Figure 3 As shown in Figure 3(d), the S 2p fitting results show that the fitting peaks at 162.38 eV and 168.38 eV represent SC and S, respectively. 2- .
[0040] 2. Performance evaluation Figure 4 For PI / AGO series samples in K-band and Ka-band ε' 、 ε" and tan δ ε The curve of value changing with frequency. Figure 4 (a) and Figure 4 (d) shows that all samples ε' In the K-band range, there is an upward trend, and all ε' All of them vary in the range of 3.75-7.5. Figure 4 (b) and Figure 4 In (e), PI / AGO-2.0 has high ε"value, indicating that it may have a higher loss capacity for electromagnetic waves, and its maximum value is 2.94. ε' and ε" The change of the value shows a flat trend, which means that the speed of polarization inside the material cannot keep up with the rate of change of the electromagnetic field, resulting in polarization relaxation and energy loss. Figure 4 (c) and Figure 4 (f) shows the tan of PI / AGO-2.8 δ ε The values are greater than those of all other samples in both the K-band and Ka-band, indicating that it has the largest dielectric loss capability among all samples. A heterogeneous interface is formed between AGO and PI, thereby enhancing the interface polarization.
[0041] Figure 5 For PI / S-AGO series samples ε' 、 ε" and tan δ ε The curves of K-band and Ka-band with frequency. As shown in 5(a) and 5(d), the PI / S-AGO sample is in the range of 4-9.77, which is higher than the 3.75-7.5 of PI / AGO. In 5(b) and 5(e), the PI / S-AGO sample is in the range of 4-9.77, which is higher than the 3.75-7.5 of PI / AGO. ε" The maximum value is 4.21, which is 1.43 times higher than the 2.94 of PI / AGO, indicating that the PI / S-AGO sample has a stronger dissipation ability for electromagnetic waves. ε" The curve has fluctuations, which may be due to the dielectric loss caused by conductive loss and polarization loss. Since atomic polarization and electronic polarization can be ignored in the microwave range (1-300 GHz), the polarization loss in 18-40 GHz is mainly dipole polarization and interface polarization. In addition, it can be clearly seen that ε" The fluctuations within the Ka band are significantly more numerous and stronger than those within the K band. ε" The value fluctuates, indicating a higher electromagnetic wave loss capability in the Ka band. In addition, a heterogeneous interface exists between S-AGO and PI, which induces interfacial polarization. The defects and functional groups formed by the S atoms in S-AGO promote the dipole polarization caused by electron hopping and migration.
[0042] Figure 6 The Cole-Cole curves of PI / AGO-1.6 in the (a) K band and (b) Ka band are shown. It can be seen that the Cole-Cole curves in all bands have a semicircular structure, and the semicircle of the Cole-Cole curve in the Ka band has a larger radius, indicating a stronger polarization relaxation process.
[0043] Figure 7 The Cole-Cole curves of PI / S-AGO composite films with different S-AGO contents in the K band are shown. The "tailing" phenomenon at the end of the curve indicates that the material has conductive loss.
[0044] Figure 8 The Cole-Cole plots of PI / S-AGO composite films with different S-AGO contents in the Ka band are shown. Multiple semicircles are present in all samples, indicating the presence of multiple polarization relaxation processes. This is likely due to the interfacial polarization generated by the heterostructure between S-AGO and PI, as well as the presence of defects and functional groups on S-AGO, which promote dipole polarization in the composite film. Compared to the semicircles in the K band, the semicircles in the Ka band are more numerous and have a larger radius, suggesting that the PI / S-AGO samples may have stronger polarization relaxation processes in the K band.
[0045] Figure 9 The reflection loss of PI / AGO composite film varies with thickness at different graphene contents in the K band. It can be seen that the RL of PI / AGO-1.6 at 2.5 mm and 18 GHz is min RL of PI / AGO-2.0 at 1.5mm and 19.4 GHz is -10.7 dB. min The RL of PI / AGO-2.4 at 3.5 mm and 25.5 GHz is -24.2 dB, and its corresponding EAB is 4.45 GHz. min The RL of PI / AGO-2.8 at 1.75 mm and 18.3 GHz is -33.3 dB, and its corresponding EAB is 2.5 GHz. min is -25.3 dB, and the corresponding EAB is 3.63 GHz. At the same time, the RL at 1.5 mm and 21.41 GHz is min The EAB is 18.7 dB, and the corresponding EAB can reach 6.03 GHz.
[0046] Figure 10 The reflection loss diagram of PI / S-AGO series samples in K band varies with thickness. When the frequency is 25.95 GHz and the thickness is 3.5 mm, the RL min The RL of PI / S-AGO-2.0 is -25.3 dB and the EAB is 1.79 GHz. min The RL of PI / S-AGO-2.4 is -16.6 dB and the EAB is 1.24 GHz. minThe RL of PI / S-AGO-2.8 is -26.3 dB and the EAB is 5.82 GHz. min The K-band reflection loss of the PI / AGO composite film increased from -33.3 dB to -53.6 dB, and the EAB was 3.43 GHz. This increase was 1.61 times greater than the original value. This is likely due to the fact that S doping into AGO introduces defects and polar functional groups, increasing its conductivity and improving impedance matching, thereby enhancing its absorption performance.
[0047] Figure 11 The reflection loss diagram of samples with different PI / AGO contents in the Ka band varies with thickness. It can be seen that the RL of PI / AGO-1.6 at 3 mm and 36.7 GHz is min The RL of PI / AGO-2.0 at 1.18 mm and 26.5 GHz is -20.9 dB, and its corresponding EAB is 4.77 GHz. min The RL of PI / AGO-2.4 at 3.5 mm and 27.3 GHz is -18.6 dB, and its corresponding EAB is 3.5 GHz. min is -48.1 dB, and the corresponding EAB is 5.5 GHz; the RL at 3.1 mm and 30.5 GHz min The RL at 2.51 mm and 36.1 GHz is -61.2 dB, and the corresponding EAB is 4.4 GHz. min The RL of PI / AGO-1.6 at 33.2 GHz is -58.9 dB, and its corresponding EAB is 4.63 GHz. min The value is -14.6 dB, and the EAB is 8 GHz. Compared with the reflection loss value in the K band, the RL of all samples in the Ka band is min Both have been improved, indicating that PI / AGO has better wave absorbing performance in the Ka band, and the PI film composited with AGO is more conducive to absorbing electromagnetic waves at high frequencies.
[0048] Figure 12 The reflection loss diagram of PI / S-AGO series samples in Ka band varies with thickness. When the frequency is 34.8 GHz and the thickness is 3.15 mm, the RL min The RL of PI / S-AGO-2.0 is -65.8 dB and the EAB is 6.42 GHz. At this time, PI / S-AGO-2.0 has the best reflection loss value among all PI / S-AGO samples. When the frequency is 29.59 GHz and the thickness is 3.5 mm, the RL of PI / S-AGO-2.0 is -65.8 dB and the EAB is 6.42 GHz. minThe RL of PI / S-AGO-2.4 is -18.9 dB and the EAB is 4.27 GHz. min is -31.9 dB, EAB is 5.21 GHz; at a frequency of 33.12 GHz and a thickness of 0.9 mm, RL min The RL of PI / S-AGO-2.8 is -23.7 dB and the EAB is 10.84 GHz. min It is -54.2 dB and EAB is 10.59 GHz.
[0049] contrast Figure 11 PI-AGO products, PI / S-AGO has more advantages: Impedance matching optimization – Sulfur atoms modulate surface conductivity, enabling ultra-broadband absorption (EAB > 10.5 GHz, covering 78%+ of the Ka-band) in sub-millimeter thickness (0.9–0.94 mm). This breaks through the bottleneck of thin-layer broadband compared to undoped PI / AGO (which requires >3 mm thickness to achieve EAB < 5 GHz). Polarization loss enhancement – Sulfur defects and interfacial charge accumulation synergistically enhance dielectric loss, driving the peak absorption intensity to -65.8 dB (PI / S-AGO-1.6), which is better than the undoped optimal value of -61.2 dB; Improved high-frequency adaptability: Wavelength compatibility (0.9 mm matches λ≈10 mm millimeter wave) overcomes the scattering and reflection problems of traditional materials in the Ka band, providing an integrated ultra-thin broadband solution for 6G communications and millimeter-wave stealth.
[0050] Figure 13 (a) and Figure 13 (b) Impedance matching diagrams of PI / S-AGO composite films in the K-band and Ka-band frequency bands respectively. in The closer the value of / Z0| is to 1, the better the impedance matching performance of the material. in The values of / Z0| are 0.897, 0.74, 0.908 and 0.996 respectively; in the range of 26.5-40 GHz, |Z in The values of / Z0| are 0.999, 0.795, 0.950 and 0.996 respectively. Figure 10 and Figure 12 The results support each other.
[0051] From the above analysis, it can be seen that sulfur-doped graphene (S-AGO) prepared by doping sulfur into amino-modified graphene (AGO) and compounding it with polyimide to prepare PI / S-AGO composite film. This material achieves a minimum reflection loss (RL) of -65.8dB at 34.8 GHz. min ), with an effective absorption bandwidth (EAB) of 6.42 GHz (corresponding to a thickness of 3.15 mm). Compared to the PI / AGO system, its absorption strength and effective bandwidth are significantly improved. The introduction of sulfur creates a large number of lattice defects and heteroatom functional groups on the graphene surface, significantly enhancing the interfacial polarization and dipole polarization effects within the material, thereby improving electromagnetic energy loss. This solves the industry's difficulty in balancing strong loss and broadband absorption in thin-layer absorbing materials, and promotes the lightweight and practical engineering of high-frequency electromagnetic protection.
Claims
1. A method for preparing a PI / S-AGO composite absorbing film, characterized in that: The following steps are involved: (1) Preparation of AGO First, graphene oxide was dispersed in deionized water and ultrasonically treated. Then, p-phenylenediamine was added and stirred in an oil bath at 75-85°C for 10-15 hours. After the reaction, the mixture was filtered, washed, and vacuum-dried to obtain amino-modified graphene oxide, denoted as AGO. (2) Preparation of S-AGO Under reflux conditions at 90-100°C, sodium polysulfide solution was added dropwise to the AGO dispersion at a rate of 1-5 mL / min for 3-6 hours. After the reaction, the mixture was filtered, washed, and vacuum-dried to obtain sulfur-doped graphene, which was designated as S-AGO. (3) Preparation of PI / S-AGO composite film First, under inert atmosphere, S-AGO was dispersed in N,N-dimethylacetamide and stirred evenly. 4,4'-diaminodiphenyl ether was added to dissolve it, and then 3,3',4,4'-benzophenonetetracarboxylic dianhydride was added in batches. The molar ratio of 4,4'-diaminodiphenyl ether to 3,3',4,4'-benzophenonetetracarboxylic dianhydride was 1:1.01-1.
05. The mixture was then reacted at a low temperature of 0-5°C for 3-6 hours and allowed to stand overnight to obtain a uniform mixed solution with an S-AGO content of 0.5-5.0 wt%, named PAA / S-AGO solution. Next, the PAA / S-AGO solution was coated to form a film. After solvent evaporation and preliminary imidization at 80-120°C, the temperature was programmed to rise to 300-400°C in a tube furnace for complete imidization to obtain a PI / Cu / S-AGO composite film.
2. The method for preparing a PI / S-AGO composite absorbing film according to claim 1, wherein: In step (1), the mass ratio of graphene oxide to p-phenylenediamine is 1:2 to 2:
1.
3. The method for preparing a PI / S-AGO composite absorbing film according to claim 1, wherein: In step (2), the concentration of the sodium polysulfide solution is 2-2.5 mol / L in terms of sodium ions, and the concentration of the AGO dispersion is 0.001-0.005 g / mL.
4. The method for preparing a PI / S-AGO composite absorbing film according to claim 1, wherein: In step (3), the inert atmosphere is argon or nitrogen, and the complete imidization procedure is: heating at 2°C / min, and keeping the temperature at 150°C, 200°C, 250°C, and 300°C for 1 hour each; when the target temperature is 400°C, continue to keep the temperature at 350°C for 10 minutes and at 400°C for 1 hour.
5. A PI / S-AGO composite absorbing film, characterized in that: Prepared by the method of any one of claims 1-4, wherein S-AGO is uniformly dispersed in the polyimide matrix and the S-AGO content is 1.6~2.8 wt%.
6. An application of the PI / S-AGO composite absorbing film according to claim 5 in the fields of 5G communication equipment, radar stealth coating or high-frequency electromagnetic shielding.